Initial Reports of the Deep Sea Drilling Project 1981
DOI: 10.2973/dsdp.proc.63.129.1981
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Properties of Igneous Rocks from Deep Sea Drilling Project Leg 63

Abstract: This study reports the magnetic properties of 30 samples of igneous rocks recovered from Sites 469 through 473 of Leg 63 of the Deep Sea Drilling Project. Such studies are relevant for determining the thickness and composition of the source layer of the marine magnetic anomalies. These studies are also relevant to the study of ophiolites, in which direct comparison of magnetic properties can lead to important inferences (e.g., Butler et al., 1976; Levi et al., 1978; Beske-Diehl and Banerjee, 1979). We made rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The WR Cs concen tration increases during palagonitization but decreases during oxidation. Such a variation was also observed in an earlier study by Verma (1981a). The decrease of Cs during oxidation is consistently observed in all leach-fractions and residues as well (Table 4; Fig.…”
Section: Ree-thesupporting
confidence: 87%
See 3 more Smart Citations
“…The WR Cs concen tration increases during palagonitization but decreases during oxidation. Such a variation was also observed in an earlier study by Verma (1981a). The decrease of Cs during oxidation is consistently observed in all leach-fractions and residues as well (Table 4; Fig.…”
Section: Ree-thesupporting
confidence: 87%
“…Dur ing oxidation of the crystalline MORB, this ratio increases only slightly from 0.70316 (for 487 LO) to 0.70325 (for 487 MO), but during palagonitization, much larger changes result. In an earlier study also, Verma (1981a) observed only a slight increase in 87Sr / 86Sr ratio from "fresh" (less -oxidized) basalt (-0 .70297) to the "oxidized" ( --0 .70312) one. The data on leach fractions (L1 and L2) also show similar trends.…”
Section: Ree-thementioning
confidence: 72%
See 2 more Smart Citations
“…Geochemical evidence of the tholeiites is compatible with their formation at a spreading center (Shibata et al, 1981). Verma and Banerjee (1981) investigated magnetic properties of the tholeiites and gave NRM data from two to four discrete samples for Holes 469, 470, 470A, and 472. Average NRM values are tabulated for individual holes in Table T1.…”
Section: Sites 469 470 and 472mentioning
confidence: 99%